Measuring the Effectiveness of public sector audit: Scale development and validation / Nor Raihana Asmar Mohd Noor and Noorhayati Mansor - Mohd Noor, Nor Raihana Asmar; Mansor, Noorhayati (Universiti Teknologi MARA Cawangan Kelantan, 2020)
There has been a growing interest in the effectiveness of public sector audit as a theoretical construct. However, despite the heightened recognition, the field still lacks a standardised measure that can be used in surveys to capture individual-level variation in the reputation judgments of public and other stakeholders. Therefore, this study aims to establish a standardised measurement of the effectiveness of public sector audit based on the conceptual definition. A survey study of 203 internal auditors and experts were carried out by employing non-probability purposive sampling. The data obtained were then interpreted based on the Partial Least Squares Structural Equation Modeling (PLS-SEM). Using the same data, a unidimensional scale of the effectiveness of public sector audit was tested. The public sector audit illustrates the content domains of internal audit quality, internal audit independence, proficiency of internal auditors and types of audit. The results suggest that the scale development and the validation of the effectiveness of public sector audit are internally reliable and that it is positively correlated with support for internal audit quality, internal audit independence, proficiency of internal auditors and types of audit. This study further recommends the extension of the scale development and validation used in this research for future researches in the private and public sector